2011
DOI: 10.1111/j.1439-0507.2011.02068.x
|View full text |Cite
|
Sign up to set email alerts
|

Early serum (1→3)‐β‐D‐glucan levels in patients with burn injury

Abstract: Serum (1→3)-β-D-glucan (BG) is increasingly used as diagnostic marker for invasive fungal infections. Exposure to gauze may lead to false-positive BG assays. The role of BG is unclear in thermally injured patients who frequently require extensive gauze coverage; therefore, we prospectively evaluated BG levels in burn-injured patients. Serum BG levels were measured in 18 burn patients immediately before application of the first dressing and 12 h after. Patients were stratified by extent of total body surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Our ICU patients showed a wide variability in terms of underlying clinical conditions and potential confounders; thus, it could be challenging to firm define the potential causes of reduced specificity. Among these potential factors, only the occurrence of severe burns and/or breakdown of mucosal integrity was independently associated with false‐positive results, confirming the very low PPVs reported in literature for burnt and trauma patients 58,59 . Overall, our data suggest that, in ICU and trauma settings, the added value of BDG quantification by Wako assay is probably more relevant to exclude than to prove IFI.…”
Section: Discussionsupporting
confidence: 82%
“…Our ICU patients showed a wide variability in terms of underlying clinical conditions and potential confounders; thus, it could be challenging to firm define the potential causes of reduced specificity. Among these potential factors, only the occurrence of severe burns and/or breakdown of mucosal integrity was independently associated with false‐positive results, confirming the very low PPVs reported in literature for burnt and trauma patients 58,59 . Overall, our data suggest that, in ICU and trauma settings, the added value of BDG quantification by Wako assay is probably more relevant to exclude than to prove IFI.…”
Section: Discussionsupporting
confidence: 82%
“…A 12 h BDG was positive in 8 ⁄ 19 patients and was not related to gauze coverage. 24 Detection BDG in the serum of patients from surgical intensive care unit were reported as a useful tool to aid in the early diagnosis of invasive candidasis, however a sampling interval of 3-4 days post surgery was recommended to allow BDG leached from surgical sponges and gauze to fall to background levels. 25 Racil and collagues 26 reported a high rate of false BDG results in patients at risk for IFI.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested that BG is undetectable in normal CSF (11). False-positive test results occur in serum assays in association with a number of conditions (12)(13)(14). We do not yet know whether CSF false positives would occur due to biologic variables in the CSF or from other events in sample processing such as the use of cotton gauze or a cotton alcohol swab to clean the puncture site in the LP procedure, but these cases illustrate an association between detectable results and suspected disease.…”
mentioning
confidence: 99%